Noninfectious complications of central venous lines in children with cancer – single center experience - Panas, Agata; Krawczuk-Rybak, Maryna; Muszyńska-Rosłan, Katarzyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
Introduction: Multidrug chemotherapy in children requires central venous line access, which generates potential risk for many complications. Aim of the study was analysis of frequency and type of complications ocurring due to central venous lines in children treated for pediatric malignancies at the Department of Pediatric Oncology and Hematology, Childrens’ Teaching Hospital in Białystok. Material and methods: The study group consisted of 158 patients (66 girls, 92 boys) who had implanted, in total, 217 central venous lines accesses. Among these lines 150 were tunneled catheters of Broviac type and 67 subcutaneous ports. Observed complications included infections, thrombosis, mechanic damage and blocked flow in the line. The risk factors analysis focused on type of malignancy, type of the central line access and tender. Results: 50/158 (31.64%) patients, both boys and girls (no preferences with the gender was noted), from the studied group had no complications concerning central line access. In 83 patients one complication was observed – 31 (46.26%) in subcutaneous ports cases and 52 (34.66%) in catheters. More than one complication was observed in 25 patients – 11 (17.7%) in subcutaneous ports cariers and 14 (14.58%) in patients with catheters. Among 136 observed central line complications 65 (47.8%) were due to infection, 34 (25%) were mechanical dysfunction of the device, 22 (16.2%) were blocked flow in the line, in 9 cases (6,6%) thrombosis was found and in 6 (4.4%) cutaneous changes in the skin above the port were found. Due to complications 79 (50%) catheters were removed. The most common causes for removal were: infection (n = 51, 32.3%), mechanical dysfunction (n = 23, 14.5%) and thrombosis (n = 3, 1.9%). Mechanical dysfunctions were more prevalent in patients with tunneled catheters than with ports. Removal of the device due to mechanical dysfunctions was twofold greater in boys than in girls. The necessity for removal and implantation of the new central line was more often observed in patients treated for leukemias. Conclusions: Central venous lines provide better quality of life for patients during anticancer treatment, but are also cause of many complications, especialy in children treated for hematological malignancies.